DATA RECOVERY APPLICATION FROM NAND FLASH MEMORIES USING THE CHIP-OFF TECHNIQUE IN DIGITAL FORENSICS - Avanoz, Tahire; Akbal, Erhan (My University, 2025)
In digital forensics, retrieving data from physically damaged or inaccessible devices is critical for evidence preservation. This study presents a detailed application of the chip-off technique for data recovery from NAND flash memories. The process involves the physical removal of a TSOP-48 NAND chip from a defective SanDisk flash drive, followed by cleaning, preparation, and raw data extraction using the PC- 3000 Flash platform. Each stage — including soldering temperature adjustment, pin cleaning, ECC correction, and XOR decoding — is described step by step to ensure repeatability and data integrity. Experimental findings show that using optimal rework parameters (380 °C, 30 % airflow) and proper flux (Amtech NC-559-ASM) allows for complete and error-free data recovery. The study emphasizes the importance of standardized chip-off procedures in forensic laboratories and provides practical guidance for minimizing physical and logical errors during the recovery of NAND-based storage devices.
Keywords: Digital forensics; data recovery; Chip-off